Barriga solidária: limites jurídicos e o direito fundamental ao próprio corpo - Silva, Eneida Rosélia Nascimento (2016)
This study aims to verify the (im) possibility of alienation of the fundamental right to the body under the central focus of surrogacy or solidarity belly, addressing the need or not to build a specific regulatory system. To do so will be raised studies on how the possibility of alienation of a fundamental right takes place within our society with the financial goal, disregarding often ethical, moral, legal and social values, often making women vulnerable against current bioethical developments. data and documents will be presented in order to verify that the current regulations in Brazil is sufficient for effective control of body disposal of possibility in cases of surrogacy. Depending on the technical procedures to work, the research involved literature, consisting primarily analysis of books, journal articles and materials available on the Internet; documentary, with analysis of Brazilian legislation and other countries, about the surrogacy. The method used is the inductive which is based on observation of particular facts and realities notes the existence of disposal of cases across the board. The search result has the function to inform on the need for a mechanism to force Act in order to make more effective and efficient control over these technological advances that grow increasingly in our society.